2022
DOI: 10.21203/rs.3.rs-2145478/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Ultra-Energy-Efficient Reversible Designs of Sequential Logic Quantum-Dot Cellular Automata Flip-Flop Circuits

Abstract: Quantum-dot cellular automata (QCA) is a technological approach to implement digital circuits with exceptionally high integration density, high switching frequency, and low energy dissipation. QCA circuits are a potential solution to the energy dissipation issues created by shrinking microprocessors with ultra-higher integration densities. Current QCA circuit designs are nonreversible, yet reversible circuits are known to increase energy efficiency. Thus, the development of reversible QCA circuits will further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…QCADesigner-E 2.2 uses a microscopic quantum mechanical model of tunnelling inside a QCA cell, along with the intra-and intercell electrostatic interactions, and a density matrix description of energy dissipation within a phenomenological model [30]. Our earlier paper [17] provides more details on the energy dissipation treatment within the quantum mechanical coherence vector formalism for the density matrix.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…QCADesigner-E 2.2 uses a microscopic quantum mechanical model of tunnelling inside a QCA cell, along with the intra-and intercell electrostatic interactions, and a density matrix description of energy dissipation within a phenomenological model [30]. Our earlier paper [17] provides more details on the energy dissipation treatment within the quantum mechanical coherence vector formalism for the density matrix.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Theoretically, reversible computing operations, in which reversibility is maintained from the logic synthesis level down to the physical layout level, result in no information loss and consequently zero energy dissipation into the environment [13]. Several studies have simulated QCA digital circuits with extremely low energy dissipation by utilising logically and physically reversible design techniques [14][15][16][17][18]. These reversible design techniques use reversible majority gates, which recycle the input signals, as the main building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that combinational QCA circuits that are both logically and www.videleaf.com physically reversible can operate with energy dissipation values lower than Landauer's limit. Later, researchers implemented this technique to develop more sophisticated combinational QCA logic circuits, as well as sequential QCA circuits, characterized by feedback loops [21,22]. In this research, we introduce the first multilayer reversible QCA ALU built using the logically and physically reversible QCA design technique.…”
Section: Introductionmentioning
confidence: 99%